2022
DOI: 10.1073/pnas.2025710119
|View full text |Cite
|
Sign up to set email alerts
|

Identification of alternative protein targets of glutamate-ureido-lysine associated with PSMA tracer uptake in prostate cancer cells

Abstract: Prostate-specific membrane antigen (PSMA) is highly overexpressed in most prostate cancers and is clinically visualized using PSMA-specific probes incorporating glutamate-ureido-lysine (GUL). PSMA is effectively absent from certain high-mortality, treatment-resistant subsets of prostate cancers, such as neuroendocrine prostate cancer (NEPC); however, GUL-based PSMA tracers are still reported to have the potential to identify NEPC metastatic tumors. These probes may bind unknown proteins associated with PSMA-su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
(67 reference statements)
1
13
0
Order By: Relevance
“…For this study, we utilized well-characterized patient-derived xenografts (PDXs) from the Living Tumor Laboratory. 1820 As shown in Fig 1a most of the xenografts, including all the neuroendocrine prostate models used in this experiment were PSMA-negative, but most showed high expression of CD46. Our previous study reported that PSMA-positive and PSMA-negative xenografts could be readily detected with a CD46 PET scan using [ 89 Zr]DFO-YS5 probe, including the LTL-331, LTL-331R, and LTL-545 models.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…For this study, we utilized well-characterized patient-derived xenografts (PDXs) from the Living Tumor Laboratory. 1820 As shown in Fig 1a most of the xenografts, including all the neuroendocrine prostate models used in this experiment were PSMA-negative, but most showed high expression of CD46. Our previous study reported that PSMA-positive and PSMA-negative xenografts could be readily detected with a CD46 PET scan using [ 89 Zr]DFO-YS5 probe, including the LTL-331, LTL-331R, and LTL-545 models.…”
Section: Resultsmentioning
confidence: 90%
“…PSMA is a type II glycoprotein overexpressed on PCa cells. Currently, PSMA PET (positron emission tomography) imaging using 68 Ga-PSMA-11 or 18 F-DCFPyL is used in routine clinical care to localize and stage patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As could be expected from the high salivary gland uptake in the PSMA PET/CT images, xerostomia was the most frequent non-hematologic side effect in this study, though serum amylase level was not checked for the diagnosis. Previous studies have shown high uptake of the [ 177 Lu]Lu-PSMA-based radiopharmaceuticals by the salivary glands [ 8 , 22 ]. A recent study showed that mild xerostomia occurred in 2 out of 56 patients after 3 to 4 cycles of treatment but spontaneously resolved before 3 months [ 23 ] and was recoverable [ 24 ], and applying external cooling with ice packs may reduce the salivary gland uptakes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A compound chemically modified to prevent degradation of NAAG, the in vivo substrate of PSMA, could become a substance that can specifically target PSMA [ 7 ]. Compounds based on glutamate-urea-lysine (GUL) structure are being studied for diagnosis and treatment of prostate cancer [ 8 ], and in particular compounds bound with radioisotopes are showing great promise.…”
Section: Introductionmentioning
confidence: 99%